Application of diversified prevention and nursing of osteoporosis in male schizophrenia patients with long-term hospitalization (多元化骨质疏松预防护理在长期住院男性精神分裂症患者中的应用) - ZHANG Xiaoning (张晓宁); ZHANG Peifeng (张培峰); TANG Xiaofang (唐晓芳) (中西医结合护理)
Objective To explore the application of diversified prevention and nursing of osteoporosis for male schizophrenia patients in long-term hospitalization. Methods Totally 66 male schizophrenia patients with long-term hospitalization were enrolled as research objects. A two-year follow-up of the diversified prevention and nursing of osteoporosis was carried out. The changes in bone mineral density were measured before and after intervention. The Positive and Negative Syndrome Scale (PANSS) was used to assess the severity of psychiatric symptoms, and Scale of Social Skills for Psychiatric Inpatients (SSPI) was used to evaluate the daily living skills and social function of patients. Results An increase in bone mineral density was observed after intervention (0. 88±0. 15 g/cm2 vs. 0. 93±0. 18 g/cm2 , P＜0. 05). The scores of positive symptom, negative symptom and general psychiatric symptom after intervention were higher than those before intervention (P＜0. 01). The scores of ability of daily living, dynamic and communicative situation, and social activity skills were higher than those before intervention(P＜0. 01). Conclusion Osteoporosis or osteopenia in male schizophrenia patients with long-term hospitalization should not be ignored. Implementation of a diversified prevention and nursing strategy can increase the bone mineral density, relieve the psychiatric symptoms and improve the daily living skills and social function of patients. (目的 探讨多元化骨质疏松预防护理在长期住院男性精神分裂症患者中的应用效果。方法 选取66名长期住院男性精神分裂症患者为研究对象, 实施多元化骨质疏松预防护理, 干预时间为2年。检测并记录干预前后患者的骨密度数据变化, 采用精神分裂症阳性和阴性症状量表(PANSS)评估患者精神症状的严重程度; 采用住院精神患者社会功能评定量表(SSPI)评估生活能力和社会功能。结果 实施护理干预后患者骨密度值为(0. 93±0. 18)g/cm2, 高于实施护理干预前的(0. 88±0. 15)g/cm2, 差异有统计学意义(P＜0. 05); 患者PANSS量表评分中阳性症状、阴性症状和一般精神病理量表评分均较干预前下降, 差异有统计学意义(P＜0. 01); 患者SSPI量表评分中日常生活能力、动性和交往情况和社会性活动技能评分均较干预前上升, 差异有统计学意义(P＜0. 01)。结论 长期住院男性精神分裂症患者的骨质疏松或骨量减少问题不容忽视。通过对其实施多元化骨质疏松预防护理, 可明显促进其骨密度增加, 改善患者精神症状的严重程度, 提高生活能力和社会功能。)